Analysis of Parking Space Needs At Ratu Jepara Market - Prayoga, Bagas; Suwandi, Putri Anggi Permata; Yudaningrum, Farida (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2023)
Abstract. Jepara Satu Market is a traditional market built by the Jepara Regency government. With the large number of sellers in the market, indirectly the number of visitors also increases every day. This is what causes Ratu Jepara Market to have the necessary facilities, namely the need for parking space. This research aims to analyze the capacity and need for parking space in the Ratu Jepara Market area and plan optimal parking patterns for motorbike and car parking. From the results of the analysis, the need for motorbike and car parking space in the Ratu Jepara Market parking area still meets existing capacity, namely of 390 SRP. The motorbike parking pattern used for on street motorbike parking in the Ratu Jepara market area uses a one-sided parking pattern, namely a 90Â° angle. Meanwhile, the on-street car parking pattern at Ratu Jepara market parking uses a 45Â° angle pattern, while the off-street car parking pattern uses a 90Â° angle parking pattern.Keywords: Need for parking space, Ratu Jepara Market, Parking area